Pemanfaatan Media Sosial dalam Kampanye Politik Menjelang Pemilu 2024: Studi Kasus tentang Akun Media Sosial Partai Politik dan Politisi - Deden Fahruji; Atef Fahrudin (Universitas Majalengka, 2023)
This research aims to uncover the use of social media by political parties and politicians leading up to the 2024 Elections using qualitative research methods and a case study approach. In the context of the evolving digital era, social media has become a primary tool in modern political campaigns. This study analyzes how major political parties and politicians utilize social media platforms such as Facebook, Twitter, Instagram, and TikTok to establish their presence, engage with voters, and promote their political messages. Through the collection and qualitative analysis of data, including social media content and observations, this research provides insights into the strategies of using social media in political campaigns and their impact on the democratic process. The research findings indicate that 18 National Political Parties and politicians who are potential presidential candidates in the 2024 Elections have actively utilized social media platforms like Facebook, Instagram, Twitter, and TikTok in their political campaigns. The Gerindra Party dominated in having the highest number of followers on Facebook, Instagram, and Twitter, while the Indonesian Democratic Party of Struggle (PDI Perjuangan) led in TikTok. Additionally, Prabowo Subianto had the most followers on Facebook, Ganjar Pranowo on Instagram, Anies Baswedan on Twitter, and Ganjar Pranowo maintained the lead on TikTok. These findings reflect the varying strategies employed by each candidate in using social media for their political communication in the lead-up to the 2024 Elections.